Optimization of polymer composite forming parameters for bipolar plate fabrication - Thongsuros S. (2014)
The objective of this research is to implement the design of experiment method to optimize the forming conditions of bipolar plate fabrication for PEMFC, based on a compression of polymer composite materials. The polymer composite made from epoxy resin mixed with graphite powder, with 1:3 weight ratios. The dimension of specimen is 5 cm 5 cm in width and 5 mm thick. The flow field area is 70 mm 70 mm with serpentine flow scheme. Each flow channel is 11 mm in width and depth. Three factors are studied, consisting of compression pressure, compression time and compression temperature. Surface roughness and plate flatness are the responses of the experiment. The optimal conditions were found at 1400 lb/in2 compression pressure, 5 minute compression time at 125°C compression temperature. At this point, the surface roughness of the specimen was 1.48 m and the average deviation of plate flatness is 0.15 mm. © 2011 IEEE.